Chair's note: moving forwards amidst the British International Research Institutes (BIRI) of the British Academy. (November 2019) - Atkinson, David
Abstract: This third Chair's note on the society's activities outlines the wider context of The Society for Libyan Studies within the British Academy's British International Research Institutes (BIRI), and recent developments within this collaboration. The BIRI comprises seven units that are part-funded by the British Academy and that are spread across Southern Europe, Africa and the Middle East. This note outlines the BIRI briefly, and also describes the recent developments that have seen the BIRI begin to explore how they might coordinate their work and their futures more coherently. The BIRI context is key to SLS's future and this note therefore outlines these recent developments. Abstract : إن الملاحظة الثالثة للرئيس هذه، حول أنشطة الجمعية، تتناول السياق الأوسع لجمعية الدراسات الليبية داخل معاهد البحوث الدولية البريطانية (BIRI) التابعة للأكاديمية البريطانية، والتطورات الأخيرة لهذا التعاون . تضم معاهد BIRI سبع وحدات تمول بتمويل جزئي من الأكاديمية البريطانية و تنتشر في جميع أنحاء أوروبا الجنوبية وأفريقيا و الشرق الأوسط. تتناول هذه الملاحظة معاهدBIRI باختصار، وتصف أيضاً التطورات الأخيرة التي شهدت بدء معاهد BIRI في استكشاف كيفية تنسيق عملها ومستقبلها بشكل أكبر. يعد سياق معاهد BIRI مفتاحاً لمستقبل جمعية الدراسات الليبية، و بالتالي تتناول هذه الملاحظة التطورات الأخيرة بهذا الشأن .